Schelling & Plato - Harry, Chelsea (Palgrave handbooks in German idealism, 2026)
Keywords: Dialectic; Mythology; Natural (archaeology); Opposition (politics); Reflexive pronoun; dept.phi

Has εὐβίοτος in Aristotle’s Historia Animalium ix Been Mistranslated? - Harry, Chelsea (Journal of Ancient Philosophy, 2025)
Le terme εὐβίοτος, « bien vivre », et ses équivalents apparaissent dans les observations d'Aristote sur les oiseaux, dans l'Historia Animalium IX. Cette note de recherche compare la façon dont le terme aristotélicien a été traduit dans les manuscrits grecs, latins et arabes, ainsi que dans les traductions modernes et contemporaines en anglais, français et allemand, et démontre qu'il a été mal traduit, à commencer par les traducteurs humanistes du XVe siècle, Georges de Trébizonde et Théodore Gaza. Les libertés prises dans la surinterprétation du terme aristotélicien ont peut-être obscurci ce qu'il cherchait à communiquer sur les capacités des oiseaux.
Keywords: Art; Epistemology; Literature; Philosophy; dept.phi

John Dewey - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Epistemology; Philosophy; Sociology; dept.phi

John Locke - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Philosophy; Political science; Sociology; dept.phi

Zeitloser Gegenstand - Haitos, Alexander (J.B. Metzler eBooks, 2025)
Keywords: Philosophy; Political science; dept.phi

Human Intelligence and Artificial Intelligence in Collaboration: Change Management, Creative Performance, and Societal Expectations - Goralski, Margaret; Górniak-Kocikowska, Krystyna (Future of business and finance, 2026)
Keywords: Applications of artificial intelligence; Artificial intelligence; Artificial psychology; Change management; Collaboration; Creative performance; Creativity; Human intelligence; Societal expectations; dept.phi

Living well in extended reality: Training phronesis and Socratic humility in XR - Gabriels, Katleen; Volkman, Richard (Journal of Moral Education, 2025)
Practical wisdom is the intellectual virtue relating to the ability to fix ends and discern in a concrete circumstance how to achieve those ends. It is cultivated through engagement with experience rather than book learning. However, a whole matrix of convergent technologies, such as headsets, haptic suits, AI-driven chatbots, and extended realities, such as augmented and virtual reality (AR/VR), creates new conditions for training practical wisdom. How can moral educators facilitate practical wisdom in this extended reality (XR)? Drawing on Nussbaum’s account of phronesis, we contend the job of moral education in XR is mostly about ensuring students’ critical engagement. We suggest AI assistants can contribute to this task, so long as these technologies and the people using them manifest Socratic humility ensuring that no single interaction serves as an ‘oracle of truth’, leaving critical thinking and judgment firmly in the hands of the student.
Keywords: Environmental ethics; Epistemology; Extended reality; Humility; Hypocrisy; Pedagogy; Philosophy; Phronesis; Psychology; Social psychology; Sociology; Socratic humility; Socratic method; Theology; Training (meteorology); convergence; dept.phi; phronesis

Denialism and its consequences: the epistemic injustice of national narratives - Marsoobian, A.T. (Pragmatism Today, 2024)
An analysis of how national narratives are inevitably forms of epistemic injustice, depriving individuals of epistemic and moral agency. Denying access to knowledge about the past is a tool of all autocratic regimes, commonly used for the purpose of retaining power and exerting dominance over individuals or groups subordinate to the ruling elite. Yet such narratives and the falsifications used to buttress them, are not the exclusive instruments of autocracies but can be found to pervade the national narratives of what we often nominally label as democracies. The denial of crimes against humanity and genocide are the most egregious examples of the harms perpetrated against victims and survivors. Miranda Fricker’s writings on epistemic injustice are employed in the analysis. Turkish and Azerbaijani genocide denial of the Armenian Genocide are used to illustrate how epistemic injustice lies at the heart of denialism. © 2024 Central European Pragmatist Forum. All rights reserved.
Keywords: Melanie Altanian; Miranda Fricker; denialism; dept.phi; epistemic injustice; genocide; national narratives; peer-reviewed

Team building-it is all about people, the mission, and values - Goralski, M.A.; Górniak-Kocikowska, K. (Technology Entrepreneurship in Theory and Practice: Perspectives in Science and Engineering, 2025)
Keywords: dept.phi

Reframing the issue in 13.18 of the analects of Confucius: family privileges in criminal litigation and the Confucian insight - Yang, Xiaomei (Dao, 2024)
The sheep case in Analects 13.18 has generated a heated debate in contemporary Chinese philosophy for more than a decade. One side in this debate criticizes Confucius’ view in the sheep case and the other side defends Confucius’ position. Neither side’s reading of 13.18 is satisfactory. I argue that something important in the text has been overlooked and this omission may explain why neither side gives a satisfying reading. I offer in this essay a new reading of the sheep case which pays attention to what the existent interpretations have overlooked in the text. This new focus will give us a new perspective to reframe the issue in question and to defend the Confucian position in a more convincing way. On the new interpretation, Confucius’ position in the sheep case suggests a sensible and reasonable way for the state to balance some important social interests which the state seeks to protect.
Keywords: Criminal prosecution; Family privilege; Filial piety; Sheep case; dept.phi; peer-reviewed

Aesthetics - Marsoobian, A.T. (The Bloomsbury Handbook of Pragmatism, 2024)
Keywords: dept.phi

The power of personal archives in witnessing, teaching, and visual storytelling: the Armenian memory project - Masud, Catherine; Marsoobian, Armen T (Journal of Human Rights Practice, 2024)
Abstract The Armenian Memory Project (AMP) is a collaborative effort designed to harness the energy and resources of the University of Connecticut and the New England Armenian community for the goal of fostering greater understanding of the region’s Armenian cultural heritage and the impact human rights crimes had on the Armenian community. In 2019, students and faculty from the university worked with Armenian American institutions and individuals on an initial component of the AMP, employing digital media technology to tell the story of one immigrant Armenian family, the Dildilians. A unique course was created to produce a documentary film centring around this family’s experiences in Ottoman Turkey before, during, and after the Armenian Genocide. Designed and taught by a documentary filmmaker with support from a family archivist/historian, the course brought students together in a collaborative learning experience. By immersing themselves in the family’s extensive photograph archive, these students came to understand the important role that the past continues to play in the lives of present-day Armenians. Furthermore, by taking on the responsibility as storytellers of the Dildilian narrative, students developed a deeper identification with this distant history and, in a wider sense, an appreciation for the ethical value of memory in bearing witness to the past. This collaborative and participatory framework for teaching using archival collections can serve as a model for creating a transformative learning experience in the study of human rights, war, and genocide.
Keywords: dept.phi; peer-reviewed

Introduction - Harry, C.C.; Vlahakis, G.N. (Women in the History of Philosophy and Sciences, 2023)
Since the last quarter of the twentieth century there has been growing interest in women’s contributions to the histories of science, philosophy, and literature dating back to the very beginnings of these disciplines. This volume offers a contemporary, multinational, multidisciplinary exploration of some of these "hidden figures". © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: dept.phi

On the Perception of Time in Ancient Greece - Harry, Chelsea C (In Anderen Zeiten/In Other Times: Zeitdiskurse im Wandel/ Changing Discourses of Time across Human History, 2022)
Keywords: dept.phi

Schelling and Plato - Harry, Chelsea C (Palgrave Schelling Handbook, 2023)
Keywords: dept.phi

New Sappho as a Philosopher of Time? - Harry, Chelsea C (Women in the History of Philosophy and Sciences, 2023)
Keywords: dept.phi

Sappho of Lesbos and the Time of Erosophy - Harry, Chelsea C (Routledge Handbook on Women and Ancient Greek Philosophy, 2024)
Keywords: dept.phi

Introduction: Schelling and the Environment - Harry, Chelsea C. (Environment, Space, Place, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Brill's Companion to the Reception of Presocratic Natural Philosophy in Later Classical Thought - Harry, Chelsea C; Habash, Justin (Brill, 2021)
Keywords: Ancient Philosophy; Classical Studies; Classical Tradition & Reception Studies; History; History of Science; Philosophy; Philosophy of Science; dept.phi

Exploring the Contributions of Women in the History of Philosophy, Science, and Literature, Throughout Time - Harry, Chelsea C.; Vlahakis, George N. (Springer, 2023)
This book explores contributions by some of the most influential women in the history of philosophy, science, and literature
Keywords: dept.phi

Genocide by other means: heritage destruction, national narratives, and the Azeri assault on the indigenous Armenians of Karabakh - Marsoobian, Armen T. (Genocide Studies International, 2023)
The propaganda efforts of the authoritarian Aliyev regime in Baku and the general Western ignorance of the history of the South Caucasus have contributed to the lack of meaningful response to the genocidal aggression that Azerbaijan has inflicted on the indigenous Armenians of Artsakh, known to many as Nagorno-Karabakh. The humanitarian crisis created by the Azeri blockade of the Lachin Corridor is only the most recent step in a process of cleansing the region of its Armenian population, a process that began in the early years of the twentieth century. The Ottoman Turkish genocide of Armenians in 1915–1923 is not a distinct event of the past but a process whose ideology is central to the Azeri-Turkish genocidal violence perpetrated against Armenians in the present. An integral component of the processes of genocide is cultural heritage destruction as noted by Raphael Lemkin. The erasure of most signs of the indigenous Armenian presence on its historic homeland was particularly pronounced in the decades following the Armenian Genocide and continues today. Cultural erasure went hand in hand with Turkish state genocide denial and the rewriting and mythologizing of its national narrative. Azerbaijan has been following a similar playbook since the collapse of the Soviet Union. These genocidal processes of denial, heritage destruction, and the rewriting of history are what I describe as “genocide by other means.”
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi; genocide; heritage destruction; national narratives; peer-reviewed; violence

Why Controlling the Historical Narrative Matters: A Jamesian Response - Marsoobian, A.T. (Pragmatism Today, 2022)
An examination of the lessons learned from William James’s oration on the dedication of the Civil War Monument memorialization Colonel Robert Shaw and the Fifty-Fourth Regiment Massachusetts Infantry, an all-Black unit. The role of monuments in making visible the values of a society is explored in the context of promoting a nation’s historical narrative, in particular in their propagation of the South’s Lost Cause narrative. The genocidal violence against Armenians in the Caucasus by the Azerbaijani regime serves as the second illustration of the abuse of historical narratives. © 2022 Central European Pragmatist Forum. All rights reserved.
Keywords: Armenians; Azerbaijan; Civil War monuments; William James; civic courage; dept.phi; genocidal violence; historical narratives; peer-reviewed; the Lost Cause; ⛔ No DOI found

Ai moral enhancement: upgrading the socio-technical system of moral engagement - Volkman, Richard; Gabriels, Katleen (Science and Engineering Ethics, 2023)
Several proposals for moral enhancement would use AI to augment (auxiliary enhancement) or even supplant (exhaustive enhancement) human moral reasoning or judgment. Exhaustive enhancement proposals conceive AI as some self-contained oracle whose superiority to our own moral abilities is manifest in its ability to reliably deliver the ‘right’ answers to all our moral problems. We think this is a mistaken way to frame the project, as it presumes that we already know many things that we are still in the process of working out, and reflecting on this fact reveals challenges even for auxiliary proposals that eschew the oracular approach. We argue there is nonetheless a substantial role that ‘AI mentors’ could play in our moral education and training. Expanding on the idea of an AI Socratic Interlocutor, we propose a modular system of multiple AI interlocutors with their own distinct points of view reflecting their training in a diversity of concrete wisdom traditions. This approach minimizes any risk of moral disengagement, while the existence of multiple modules from a diversity of traditions ensures pluralism is preserved. We conclude with reflections on how all this relates to the broader notion of moral transcendence implicated in the project of AI moral enhancement, contending it is precisely the whole concrete socio-technical system of moral engagement that we need to model if we are to pursue moral enhancement.
2 citations (Crossref) [2023-10-31]
Keywords: AI socratic interlocutor; Artificial intelligence; Artificial moral agent; Moral enhancement; dept.phi; peer-reviewed

The social self and social death: Rethinking reparations for genocide and crimes against humanity - Marsoobian, A.T. (Pragmatism Today, 2020)
Based on a pragmatist inspired conception of the social self, the concept of reparations for the harms of genocide is reexamined. Both Raphael Lemkin, the person who invented the term “genocide,” and Claudia Card, a philosopher who examined the evil of genocide, hold similarly expansive notions of the harms inflicted by genocidal violence. Both argued that biological death is not necessarily central to genocide. For Lemkin cultural destruction of the targeted group is just as essential as the actual killing itself. Genocide is a group crime that aims to destroy the group and all the social aspects of group identity. Card similarly sees the target of genocidal violence as the social vitality of the self. This vitality is sustained by group relations. Reparations thus need to be reconceptualize in terms of the restoration of social life of the victim group and not solely on the basis of economic losses. Examples are given for the reparation of the social vitality of communities that have suffered genocide. © 2020 Central European Pragmatist Forum. All rights reserved.
Keywords: Claudia Card; Genocide; Raphael Lemkin; Reparations; Social death; Social self; dept.phi; peer-reviewed; ⛔ No DOI found

Global ethics for the digital age – flourishing ethics - Kantar, N.; Bynum, T.W. (Journal of Information, Communication and Ethics in Society, 2021)
Purpose: The purpose of this paper is to explore an emerging ethical theory for the Digital Age – Flourishing Ethics – which will likely be applicable in many different cultures worldwide, addressing not only human concerns but also activities, decisions and consequences of robots, cyborgs, artificially intelligent agents and other new digital technologies. Design/methodology/approach: In the past, a number of influential ethical theories in Western philosophy have focused upon choice and autonomy, or pleasure and pain or fairness and justice. These are important ethical concepts, but we consider “flourishing” to be a broader “umbrella concept” under which all of the above ideas can be included, plus additional ethical ideas from cultures in other regions of the world (for example, Buddhist, Muslim, Confucianist cultures and others). Before explaining the applied approach, this study discusses relevant ideas of four example thinkers who emphasize flourishing in their ethics writings: Aristotle, Norbert Wiener, James Moor and Simon Rogerson. Findings: Flourishing Ethics is not a single ethical theory. It is “an approach,” a “family” of similar ethical theories which can be successfully applied to humans in many different cultures, as well as to non-human agents arising from new digital technologies. Originality/value: This appears to be the first extended analysis of the emerging flourishing ethics “family” of theories. © 2021, Emerald Publishing Limited.
6 citations (Crossref) [2023-10-31] tex.author_keywords: Digital ethics; Ethical anomalies; Flourishing ethics; Global information ethics; Just consequentialism; Robot ethics tex.document_type: Article tex.source: Scopus
Keywords: dept.phi; peer-reviewed

The roman catholic church in poland after the fall of communism - Gorniak-Kocikowska, Krystyna (Occasional Papers on Religion in Eastern Europe, 2020)
WOS:000574619500001
Keywords: dept.phi; peer-reviewed; ⛔ No DOI found

Nature, Ethics and Gender in German Romanticism and Idealism - Harry, Chelsea C. (Idealistic Studies, 2020)
0 citations (Crossref) [2023-10-31] WOS:000541068700006
Keywords: dept.phi; peer-reviewed

The problem of evil in the Neo-Confucian context: Wang Yangming’s view on evil - Yang, Xiaomei (Asian Philosophy, 2020)
Wang Yangming believes that human nature is entirely good. A question naturally arises: where is evil from? It has been argued that Wang’s idealism gives rise to the problem of evil. I first argue that the difficulty for Wang to have a coherent account of evil can be removed when his idealism is understood in a narrow sense. Second, I offer an account of Wang’s view on evil in three steps. First, I argue that evil comes from the interaction between humans and the external world according to Wang. Second, I show that given Wang’s account of human nature with three aspects, there is no contradiction between Wang’s claim that human nature is the same in everyone and Wang’s claim about differences in our natural endowment which affect our moral practice. Third, I argue that Wang’s doctrine of non-distinction of good and evil in the original substance of human nature is uniquely Confucian. © 2020 Informa UK Limited, trading as Taylor & Francis Group.
0 citations (Crossref) [2023-10-31] tex.ids: yangProblemEvilNeoConfucian2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85096538386 type: Article
Keywords: Human nature; dept.phi; idealism; origin of evil; peer-reviewed; physical nature

Breaking the silence: Memorialization and cultural repair in the aftermath of the armenian genocide - Marsoobian, Armen T. (Mass Violence and Memory in the Digital Age, 2020)
Keywords: dept.phi

Mandate interrupted: the problematic legacy of the international criminal tribunal for the former Yugoslavia - Pettigrew, David (Washington University Global Studies Law Review, 2020)
Keywords: dept.phi; ⛔ No DOI found